Adsorption of hardness salts and surfactants on the cotton fabric - E. F. Bukanova; A. A. Lapshin; I. I. Chuparin (Тонкие химические технологии, 2015)
The adsorption of the washing components solution on clean and contaminated cotton fabric in water with various hardness have been investigated. The order of magnitude of the heats of adsorption of Ca2+ salts indicates the occurrence of a chemical reaction of hardness salts with negatively charged fibers of the fabric. Addition of a complexing agent reduces the concentration of calcium salts in solution. It was shown that the adsorption of nonionic surfactant and anionic surfactant mixtures on fabrics is higher than that for individual surfactants. The presence of a binary chelator in solution increases the adsorption ability and detergency of the compositions in hard water.